Electro-Optical and Electrochemical Properties of a Conjugated Polymer Prepared by the Cyclopolymerization of Diethyl Dipropargylmalonate. (24th August 2008) - Gal, Yeong-Soon; Lee, Won-Chul; Lyoo, Won Seok; Jin, Sung-Ho; Lim, Kwon Taek; Park, Young-Il; Park, Jong-Wook
Abstract : The electro-optical and electrochemical properties of poly(diethyl dipropargylmalonate) were measured and discussed. Poly(diethyl dipropargylmalonate) prepared by (NBD)PdCl 2 catalyst was used for study. The chemical structure of poly(diethyl dipropargylmalonate) was characterized by such instrumental methods as NMR (1 H -, 13 C -), IR, and UV-visible spectroscopies to have the conjugated cyclopolymer backbone system. The microstructure analysis of polymer revealed that this polymer have the six-membered ring moieties majorly. The photoluminescence peak of polymer was observed at 543 nm, which is corresponded to the photon energy of 2.51 eV. The cyclovoltamograms of the polymer exhibited the irreversible electrochemical behaviors between the doping and undoping peaks. It was found that the kinetics of the redox process of this conjugated cyclopolymer might be controlled by the diffusion-control process from the experiment of the oxidation current density of polymer versus the scan rate.